Enhancing ERP Usage Through Absorptive Capacity: A Case Study from Indonesia Enterprise - Muhammad Gunung; Muhammad Khairunnaziri; Muhammad Hafiz; Panca O. Hadi Putra (Faculty of Computer Science Universitas Indonesia, 2024)
This research investigates the effect of individual users' absorptive capacity to the usage of Enterprise Resource Planning (ERP) at PT ABC, a transportation company in Indonesia. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). This study tests the relationships between three facets of absorptive capacity and ERP usage. This study revealed that among aspects of absorptive capacity, only the capacity associated with applying ERP knowledge directly affects ERP usage. Meanwhile, prior understanding and proficiency in integrating ERP systems have a significant indirect impact on ERP usage performance. Based on these findings, it is suggested that PT ABC strengthens individual employees' absorptive capacities and encourages them to acquire ERP expertise before implementation. Moreover, cultivating a culture that supports collaboration and knowledge sharing is crucial for maximizing the benefits of ERP systems within the organization. Implementing these strategies is expected to improve ERP adoption outcomes at PT ABC